MS-150-10-f02-018: Letter from M Jeune - Jeune, M. (Valdosta, GA: Valdosta State University Archives and Special Collections, 1895)
Letter from [Susan Elizabeth] M[ary] Jeune, Baroness St Helier [wife of Francis Jeune, 1st Baron St Helier], dated June 9, inviting Arnold to dinner Sunday June 16, [1895].
1 handwritten letter on stationary, 1 page.
Keywords: Personal correspondence; Letters; Arnold, Edwin, Sir, 1832-1904; Poets--Correspondence; Nobility--England--Correspondence